Analog class-D amplifier - Zhang, Yunfan. (2012)
Class-D amplifier is extensively acceptable in audio application due to its higher power-efficiency over its linear counterparts. The analog class-D amplifiers reported can meet the specifications of high-fidelity audio application (Power Supply Rejection Ratio (PSRR) > 70 dB and Total Harmonic Distortion (THD) ≤ 0.05%), however, a complex high-resolution Analog-to-Digital Convertor (ADC) is included in analog audio system resulting in larger die area and higher power dissipation. As for the digital class-D amplifier, its open-loop structure is sensitive to supply noise ripple while its closed-loop structure imports a Digital-to-Analog Convertor (DAC). This project pertains to the design of an emerging analog class-D amplifier, digital buffer, which is to meet the high-fidelity specifications and low hardware overhead.